On-Top Plasty at the Level of the Metatarsal Neck for Treatment of Polydactyly - Liao, Wei; Jiang, Li; Zheng, Pengfei (Frontiers in Pediatrics, 2022)
Polydactyly is a common deformity of the limbs, and excision of the extra digit has shown good results in the vast majority of patients. However, this treatment approach may not suitable for all cases of polydactyly. Some complex surgical procedures are required to treat rare forms of polydactyly and achieve satisfactory correction. Here, we report the use of on-top plasty technique for treating polydactyly between the 4th and 5th metatarsals with concomitant angulation of the 5th metatarsophalangeal joint. We performed the first osteotomy at the neck of metatarsal bone by “grafting” the distal polydactyly with the normal axis to the 5th metatarsal bone. Excision of the extra toe was accompanied by simultaneous restoration of the 5th toe axis and decrease in the width of the forefoot. Finally, both appearance and function could be improved. With this novel method, the complete osteoarticular structure and weight-bearing structure of foot were well-reconstructed. Based on the findings, we recommend that for the surgery of polydactyly, the beneficial parts should be preserved for reconstruction, and the tailored and personalized approach could be adopted.